Effect of Work Discipline and Motivation on Employee Performance at PT. Hafele Indotama (LPPM STMIK Dharmapala Riau, 2022)
The purpose of this study was to determine the effect of work discipline (X1) and work motivation (X2) partially and simultaneously on the performance of employees of PT. Hafele Indotama. The type of research used in this research is descriptive quantitative research. This study took a population of employees of PT. Hafele Indotama consists of 90 people. The methods used are observation, interviews, and questionnaires. In the results of the validity test rcount > rtabel n = 90-2 namly 88 = 0,205. The reliable test of work di discipline 0,737 > 0,60. The reliable test of work motivation 0,720 > 0,60. The reliable test of employee performance 0,656 > 0,60. The normality test Kolmogorov-Smirnov the Monte Carlo Sig. (2-tailed) and significant results are 0,205. The Work Discipline Variable has a significant effect on employee performance with regression equation Y = 23,973 + 0,470 X1. The results of the t count > t table are 2,163 > 1,986. Thus Ho1 is rejected and Ha1 is accepted, the variables of Work Motivation has no significant effect on employee performance with regression equation Y = 26,944 + 0,364 X2. The results of the t count > t table are 1,108 <1,986. Thus Ho2 is accepted and Ha2 is rejected. Work Discipline and Work Motivation variables of have a significant effect on Employee with regression equation is Y = 20,617 + 0,387X1 + 0,200X2. in the results of test f count > ftable are 4,803 > 3.10. Thus Ho3 is rejected and Ha3 is accepted, meaning that simultaneously or simultaneously the variables of Work Discipline and Work Motivation have a positive and significant effect on Employee Performance at PT. Hafele Indotama.